1993
DOI: 10.1016/0741-5214(93)90548-z
|View full text |Cite
|
Sign up to set email alerts
|

Ambient oxygen tension modulates endothelial fibrinolysis

Abstract: These data support the hypothesis of a fibrinolytic shift after altered ambient O2 tensions exposure in endothelium and demonstrate that HSVEC are more sensitive to altered O2 tension than HUVEC. Altered O2 tensions depress EC fibrinolysis in this model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 13 publications
0
39
0
1
Order By: Relevance
“…Although tPA mRNA is reportedly unchanged after endothelial exposure to anoxia (9) or hypoxia (10), the PAI-1/ tPA antigen ratio appears to be increased (10), which may contribute to the apparent hypofibrinolytic state of endothelial cells exposed to hypoxia in vitro (10). Because no similar data are available for macrophages, and our in vivo experiments suggested macrophages to be the major source of PAI-1 in (Left) PAI-1 antigen.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Although tPA mRNA is reportedly unchanged after endothelial exposure to anoxia (9) or hypoxia (10), the PAI-1/ tPA antigen ratio appears to be increased (10), which may contribute to the apparent hypofibrinolytic state of endothelial cells exposed to hypoxia in vitro (10). Because no similar data are available for macrophages, and our in vivo experiments suggested macrophages to be the major source of PAI-1 in (Left) PAI-1 antigen.…”
Section: Resultsmentioning
confidence: 55%
“…Human umbilical vein cells exposed to anoxic conditions demonstrate no change in levels of tissue-type plasminogen activator (tPA) or plasminogen activator inhibitor-1 (PAI-1) (9), although reoxygenation was associated with decreased mRNA and activity of both related to the duration of antecedent hypoxic exposure. In contrast, other studies have shown that PAI-1 mRNA is increased in endothelial cells (with an inhibition of fibrinolysis) after 24 h of exposure to an ambient oxygen concentration of 40 Torr (10).…”
Section: Introductionmentioning
confidence: 62%
“…24 -26 Ischemia in the form of reduced oxygen tension has been demonstrated to both induce synthesis of PAI-1 mRNA and antigen and reduce TPA antigen release from cultured endothelial cells. 27 It is possible that endothelial cells with the 2/2 PAI-1 genotype may be more susceptible to the effects of ischemia than other forms of the PAI-1 gene, resulting in a greater expression of PAI-1. This coupled with the reduction in TPA levels would significantly reduce fibrinolytic activity and possibly promote the early development of vasculopathy.…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41] In accord with this concept are observations of intense PAI-1 expression in endothelial cells lining neovessels within chronically organizing pulmonary thromboemboli, which are also likely to be in a proliferative stage. 8 Furthermore, local hypoxia, which has been shown to be a trigger for PAI-1 upregulation, 42,43 could be another factor responsible for the elevation of PAI-1 in the remodeling/organization regions within the thrombi.…”
Section: Discussionmentioning
confidence: 99%